Effect of biofertilizer and salinity stress on productivity and vitamin C levels of Amaranthus tricolor L. - Nadhifa Athaya Khairunnisa; Dwi Umi Siswanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Abiotic stress is one of the elements that affect plant crop output due to its productivity and environmental factors. Salinity as abiotic stressors can impair plant growth, becoming a concern in the agriculture field in recent years. Biofertilizers are reported to be capable of overcoming salinity stress. Hence, it contains microbial elements in it, play a role for the nitrogen cycle in soil, which can result in increased plant growth. Therefore, this study aimed to analyze the effect of biofertilizer and NaCl as a salinity stress factor on the growth of Amaranthus tricolor L. The biofertilizer doses utilized in this study were 10 L/ha, 20 L/ha and 30 L /ha, each in combination with basic manure fertilizer. For the salinity factor, NaCl concentrations of 2500 ppm, 5000 ppm, 7500 ppm, and 10.000 ppm were employed. Environmental characteristics, plant height, number of leaves, root length, plant dry mass, chlorophyll and carotenoid content, as well as vitamin C, were all measured. The parameters were determined quantitatively. The chlorophyll and carotenoid contents were determined using a UV-vis spectrophotometer, while vitamin C levels were determined using iodometric titration. At a 95% level of confidence, the results were examined using the one-way ANOVA approach. The results indicate that a 30 L/ha dose of biofertilizer has an effect on the chlorophyll content and root length of plants, whereas a 10 L/ha dose has an effect on the carotenoid content. The highest amaranth growth was observed when 0 L/ha biofertilizer was combined with a 7500 ppm NaCl treatment, whereas the largest number of leaves was shown when 10 L/ha biofertilizer was combined with a 2500 ppm NaCl treatment. It could be concluded that while biofertilizer has no effect on plant growth parameters, it does increase plant productivity by raising chlorophyll and carotenoid levels.